Numerical modelling of internal voids in fire exposed structures - Fonseca, E.M.M. (2010)
The study of steel structures at elevated temperatures needs the characterisation of the thermal action and the material thermal properties variation with temperature as well as the thermal conduction problem solution in a domain with well know boundary conditions. Structures may have internal voids (figure 1) filled with air (hollow columns, profile sections thermally insulated, steel pipes,…). In the presence of internal voids, the internal air temperature will be determined with some simplified formulas deduced from heat transfer equations